Revealing effective adulticides for outdoor dengue vector control at selangor hot springs - Othman, Wan Norafikah; Abdul Hamid Hasani, Narimah; Abu Bakar, Nabila; Ibrahim, Najibah; Abdul Hadi, Hazirah Nurjuani; Masliana, Muhamad; Diyanah, Sharifah Aliah; Zakaria Alia, Yasmin; Ibrahim, Yasmin zafirah; Azhar, Farah farhani; Abdul Hadi, Azahari; Mazkamal, Faiqah nadhirah; et al. (Research and Innovation Division, Universiti Teknologi MARA (UiTM) Selangor, 2025)
The susceptibility levels of an outdoor dengue vector; Aedes albopictus adult populations from four hot springs in Selangor, Malaysia towards two organochlorine, two organophosphate, two carbamate and eight pyrethroid adulticides were determined in this study. Aedes albopictus adult populations from selected hot springs were exposed to each adulticide for an hour following the procedures of adult bioassays outlined by the World Health Organization (WHO). The mortalities throughout the exposure period and at 24 h post-exposure to each adulticide were noted. The Ae. albopictus laboratory strain which represented the reference strain was fully susceptible towards all tested adulticides, except for the exposure to pyrethroid permethrin 0.25% and bifenthrin 0.2%. As for the field adult populations of Ae. albopictus, various levels of resistance against organochlorine DDT 4% and dieldrin 4%; organophosphate fenitrothion 1%; carbamate propoxur 0.1% and bendiocarb 0.1%; as well as pyrethroid permethrin 0.25%, alpha-cypermethrin 0.05% and bifenthrin 0.2% were exhibited. Complete mortalities were recorded at 24 h post-treatment among all Ae. albopictus adult populations from hot springs that were exposed to organophosphate pirimiphos-methyl 0.25% as well as pyrethroid permethrin 0.75%, deltamethrin 0.05%, lambda-cyhalothrin 0.05%, cyfluthrin 0.15% and etofenprox 0.5% which suggested that these adulticides are potentially effective in controlling Ae. albopictus populations at selected hot springs if needed in the near future. Despite zero case of mosquito-borne infection reported at selected hot springs so far, more studies on the mosquito densities at these hot springs and continuous monitoring of insecticide susceptibility among mosquito vectors from these hot springs are still vital so that effective future vector control strategies for these hot springs could be planned ahead.